The Authority to Manage Goods Confiscated by the State is Reviewed According to Government Regulation Number 27 of 2014 Concerning Management of State/Regional Property - Donald Adrian Sihombing; Sriono Sriono; Kusno Kusno (Journal of Social Research, 2023)
This study aims to know and analyze, know and analyze the scope of management of State property. As well as knowing and analyzing the provisions of legislation related to the Indra Kenz case. This research belongs to the normative type of research. So it can be seen that in article 1 paragraphs (1) and (2) it is said in one pointnyes that other legitimate acquisitions can be based on court decisions that have obtained permanent legal force, for example is State Booty/Confiscation. In addition, the implementation of criminal law functions in the Indra Kenz case has been implemented properly and in accordance with what was expected in the Preamble to the 1945 Constitution.